The cultural dimensions of prospective mathematics teachers’ beliefs: Insights from Cyprus and England - Xenofontos, Constantinos (Preschool and Primary Education, 2014)
Based on the idea that mathematics education is, in general, culturally located, this paper discusses the cultural dimensions of prospective elementary teachers’ beliefs in Cyprus and England, and how these relate to the general educational culture of the two countries. Two volunteer groups (twelve students from each country) from a notable university in each country accepted an open invitation for participation and were qualitatively interviewed. This paper discusses two common sub-themes that emerged under the general theme, Explicit Pedagogic Practice, and takes into close consideration students’ beliefs about the use of teaching resources and group work. The findings suggest that the beliefs held by each cohort are framed by the cultural-educational rhetoric of its respective country. In the conclusion of the paper, some implications about teacher education are discussed.